A Study on the Effectiveness of Debt Management and Financing Strategies in Sustaining Growth at Haldiram Foods International - Jikar, Amar Vasantaro; Tekade, Atul (Journal of Neonatal Surgery, 2025)
Exploring effective debt management and financing strategies is crucial for sustaining growth in competitive markets. This study investigates the role of structured financial planning and innovative debt solutions in fostering the expansion of Haldiram Foods International. A mixed-method approach was adopted, combining qualitative insights from industry experts with quantitative analysis of financial metrics. The findings reveal that effective debt structuring, cost minimization, and strategic reinvestment are pivotal for maintaining liquidity and operational efficiency. Additionally, the paper highlights the importance of leveraging debt instruments to fund growth initiatives without compromising financial stability. It discusses the challenges and opportunities in adopting these practices, offering a roadmap for organizations to enhance their financial performance. By aligning debt management with broader business objectives, the study provides actionable insights for businesses aiming to achieve sustainable growth in dynamic environments. The research contributes to the literature on corporate finance by showcasing the interplay between financing strategies and organizational development in the context of the Indian food processing industry.